The importance of building Aymara historical memory in primary education students from a critical bilingual intercultural curriculum approach in northern Chile - Carlos Enrique Mondaca Rojas; Elizabeth del Carmen Sánchez Gonzalez; Raúl Antonio Bustos Gonzalez (Arizona State University, 2020)
The general objective of this study is to analyze the importance of constructing an Aymara historical memory from a critical and bilingual intercultural curriculum theoretical approach for its implementation in primary education in schools in northern Chile. Methodologically, the design and construction of the proposed contents originate from a qualitative perspective in semi-structured interviews and focus group to inhabitants and organizations of the original Aymara Chilean people. This would allow the structuring of an intercultural curricular proposal based on the Aymara criteria and principles of systematization of their historical memory and indigenous knowledge from a critical theoretical perspective. Therefore, it is possible to sustain that this type of curricular model raises the possibility of eradicating the folklorization of Bilingual Intercultural Education in the classrooms of the northern border of Chile and manifesting the eventuality of being a complement to the national curriculum by developing intercultural competencies for all students from the north border of Chile.